MOTIVASI DAN PARTISIPASI MASYARAKAT DESA BULUH CINA DALAM UPAYA MELESTARIKAN HUTAN ADAT BULUH CINA KEC.SIAK HULU KAB. KAMPAR PROVINSI RIAU - Johan Wibowo; Zulfan Saam; Suardi Tarumun (Jurnal Ilmu Lingkungan, 2013)
The present research was conducted in May 2012 using a correlational method. It seeks toexamine the correlation between several variables and to indentify several factor rankings.The population and sample consisted of 60 homogenous respondents who included culturalleaders, community leaders and community living around the forest. The independentvariable is motivation including trust (X1), leadership (X2), knowledge of the environment/the use of the forest (X3), economic motive (X4) and community participation. The datawere analyzed with Path Analysis. The results show that the community in preserving BuluhCina forest is characterized by high motivation of the local wisdom. Then, there is a directand positive effect of X1, X2, X3, X4 toward the community participation level to preservethe forest. However, the participation of both local and central government is very essential topreserve Buluh Cina cultural forest with a more effective approach to the village communitymembers around the forest to grow positive attitudes and increase the community motivationto preserve the forest.